DengueTools: innovative tools and strategies for the surveillance and control of dengue - Wilder-Smith, Annelies; Renhorn, Karl Erik; Tissera, Hasitha; AbuBakar, Sazaly; Alphey, Luke; Kittayapong, Pattamaporn; Lindsay, Steve; Logan, James; Hatz, Christoph; Reiter, Paul; Rocklöv, Joacim; Byass, Peter; et al. (Taylor & Francis Open, 2012)
Dengue fever is a mosquito-borne viral disease estimated to cause about 230 million infections worldwide every year, of which 25,000 are fatal. Global incidence has risen rapidly in recent decades with some 3.6 billion people, over half of the world's population, now at risk, mainly in urban centres of the tropics and subtropics. Demographic and societal changes, in particular urbanization, globalization, and increased international travel, are major contributors to the rise in incidence and geographic expansion of dengue infections. Major research gaps continue to hamper the control of dengue. The European Commission launched a call under the 7th Framework Programme with the title of ‘Comprehensive control of Dengue fever under changing climatic conditions’. Fourteen partners from several countries in Europe, Asia, and South America formed a consortium named ‘DengueTools’ to respond to the call to achieve better diagnosis, surveillance, prevention, and predictive models and improve our understanding of the spread of dengue to previously uninfected regions (including Europe) in the context of globalization and climate change.